Witchery and Weather: Decoding the Metaphor of Drought in Silko’s Stories - Panta , Bijaya Raj (Pragnya Sarathi, 2026)
This paper analyzes the effects of colonization on Indian life as presented in Leslie Marmon Silko’s two stories, “Tony’s Story” and “Lullaby,” from Storyteller. Through close textual analysis of metaphors as informed by Gerald Vizenor’s interpretation of “witchery,” the study posits that Silko uses metaphors from nature and body, such as drought, cold, illness, and alcoholism, to show the effects of colonization. In these stories, colonial agents, including state police, government doctors, and state institutions, function as agents of witchery that disrupt Indian's relationships to land, to their past, and to their communal life. The use of metaphors is to frame a colonial power not merely as political domination but as a destructive force producing spiritual and cultural disintegration within Native communities. At the same time, Silko’s narratives exhibit ritual, storytelling, and cultural memory as counterforces capable of restoring balance and healing the effects of witchery. By interpreting witchery as a metaphor for colonial violence, the paper adds knowledge on Silko studies in relation to postcolonial epistemology.